Open-Ended Tasks Promote Creativity in Minecraft - Yue Fan (Educational Technology & Society, 2022)
Due in part to its flexibility and open design, the video game Minecraft has emerged as a popular tool for teaching and learning. Inspired by prior research showing the influence of problem-solving mindsets in physical settings, this study is an effort to understand the extent to which an open-ended task influences subsequent problem-solving behaviors in a virtual environment. Specifically, we investigate creativity and its relationship with task design in Minecraft by comparing a well-defined task group, instructed to follow step-by-step directions, with a group pursuing an open-ended task requiring a higher degree of agency. Creativity is assessed using two conventional approaches: the Alternative Uses Test (AUT) and the Consensual Assessment Technique (CAT). Judges were trained to evaluate using both methods and achieved sufficient agreement on a subset of the data prior to completing the full data set. Our results suggest that (1) participants who engaged in the open-ended task receive significantly higher CAT scores than those in the well-defined task group, and (2) among variables such as the level of skill/experience, interest in Minecraft, and materials (blocks) used in Minecraft, only game interest level has a significant influence on the CAT score.